Gender Differentials in Perceiving Climate Change Impacts in the Kaligandaki Basin, Nepal - Pandey, Rishikesh (Janapriya Journal of Interdisciplinary Studies, 2020)
The global climate system is changing faster than earlier projections with variable rates across the geographic scale. The impacts are also perceived heterogeneously across the places and communities. This study explores gender differentials in impact-perception in the Kaligandaki river valley in central Nepal. Research used primary data collected from 360 households, 75 Key Informants and 24 Focus Groups Discussion as well as through construction of nine Historical Timeline Calendars from three clusters – Meghauli (lower basin), Lumle (middlepart) and Upper-Mustang (upper-basin). The impact perception was assessed under seven social-ecological variables in the unipolar Likert Scale. The impact perception does not significantly differ across the gender of respondents while testing the means of perception scores and probably it is due to the impacts that have been experienced at profound level. The test of independence of gender to level of impacts indicates no significant association. This research also tried to check if other social-economic variables such as age of respondents and landholding size of household as well as self-reported economic status of households were significantly associated with some of the impacts. However, the number of cells with expected counts less than 5 in chi-square test turned to be more than 20 percent so they were considered to be invalid. Nevertheless, impact perception is significantly associated with the places of residence or study clusters, which indicates that local social-ecological system matters in climate change impacts. The qualitative information however, suggests otherwise that women feel higher level of risk and impacts, and is related to their concern over the welfare of family members and livelihood resources. Since risk perception is found to be related to spatial characteristics, this research recommends for development and implementation of targeted and localized adaptation policies. None the less, those policies must also recognize the women’s concerns on climate change impacts.